MENUJU KAJIAN SEJARAH LEMBAGA PERADILAN SHARÄªâAH DI KAWASAN ASIA TENGGARA (Sebuah Kajian Metodologi Sejarah Perbandingan Kawasan) - Adiwidjajanto, . Koes (Program Studi Hukum Keluarga Islam Fakultas Syariah dan Hukum, 2012)
This article is overall not the historical approach to the intriguing discussion on Islamic Jurisprudenceâbut it is real historical data which reconstruct how islamic laws was considered as applicable laws in the history of Southeast Asia region. In fact, it comprises a part of significant topics from interesting subjects that shapes the region. Historians come to agreement that Islam, as one of major living religion in the world, became substantial identity in Indonesian Archipelago, Malay ethnics in Peninsular and Chams community in southern Indochina coastal region, even as a ground for separateness in southern Philippines minority and Pattani region. This writing focuses on history how SharÄ«âah as applicable law to the local inhabitants, and its substantial role alongside âAdat lawsâ (customs) amongst Muslims Malay and Indonesia. Western penetration, which begun from last sixteenth century, did also contribute in regulation that develop a priest court, âa Muhammadan Law court,â and was adopted later by its independent successor as sharÄ«âah court. Hopefully this article becomes preliminary study on comperative history of Southeast Asia region in selected topics, for example, on subject of the development and reorganization Muhammadan law court.